1998
DOI: 10.1007/bf02299830
|View full text |Cite
|
Sign up to set email alerts
|

A computer-mediated support system for project-based learning

Abstract: Project-based learning places demands on learners and instructors that challenge the tra-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 11 publications
1
45
0
5
Order By: Relevance
“…Collaboration can be characterized by three important elements: independence [14], interdependence [15] and synthesis of information [16] . The three elements work together for effective online collaborative learning.…”
Section: B Analyzing Collaborationmentioning
confidence: 99%
“…Collaboration can be characterized by three important elements: independence [14], interdependence [15] and synthesis of information [16] . The three elements work together for effective online collaborative learning.…”
Section: B Analyzing Collaborationmentioning
confidence: 99%
“…Problem driven refers to emphasize the meaning of the problem, students find and select problem in real life; inquiry is defined middle school students to make assumptions in PBS learning activities, and to discuss the different hypotheses, design of plan or experimental scheme, information collection, analysis of data, forming a conclusion; works guide the students to complete a series of learning outcomes in explore; cooperation refers to each discussion among the students, teachers and members in the learning community; technology refers to the use of computer technology to obtain data and information [9,10].…”
Section: Pbs Teaching Patternmentioning
confidence: 99%
“…Efforts to include better preparations have begun for pre-service teachers within methods coursework and during student teaching, but the foundation needs to be laid earlier in the education program. Laffey and Musser (1998) suggested that teacher education programs need to incorporate technology into the curriculum in order to motivate teacher candidates to creatively utilize technology. Pre-service teachers who experience modeling of relevant usage of technology will be more likely to implement this approach within their own classrooms.…”
Section: Relevance and Significancementioning
confidence: 99%
“…Theorists suggest that learning is more effective when students are able to discuss their ideas, experiences and perceptions with peers (Jonassen & Kwon, 2001;Kanuka & Anderson, 1998). Some researchers have indicated that the flexibility and technological support for such interactions available in computermediated environments point to collaborative learning strategies as a promising means to implement new technology (Laffey, Tupper, Musser, & Wedman, 1998;Pena-Shaff & Nicholls, 2004;Strijbos, Martens, & Jochems, 2004;Oliver & Omari, 2001). Furthermore, theorists have indicated that CMC could have greater effects than other modes of interaction on learning in problem-solving, case study, and other higher-order learning situations (Adelskold, Alklett, Axelsson, & Blomgren, 1999;Johnston, 1996;Jonassen, Prevish, Christy, & Stavulaki, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation